STUDI KOMPARATIF ANTARA PENDAPAT MAZHAB HANAFI DENGAN SYAFI’I MENGENAI KONSEP ZAKAT KEKAYAAN ANAK-ANAK DAN ORANG GILA: Indonesia - Fariz Al-Hasni (Universitas Islam Negeri Mataram, 2022)
Zakat on wealth is one of the pillars of Islam that must be carried out by people who have a certain amount of property and reach a predetermined nisab, but the Hanafi and Shafi'i scholars have different opinions in interpreting this. Scholars of the Hanafi school are of the opinion that small children and crazy people who have assets reaching one nisab, are not subject to the obligation of zakat, because they are not required to worship, such as prayer and fasting. While the scholars of the Shafi'i school do not accept this condition, they are of the opinion that if a small child or a crazy person has assets of one nisab or more, then zakat must be issued. Their reasoning is that the sacred texts (verses and/or hadith) that oblige zakat on Muslim wealth do not differentiate whether the owner is mature and intelligent or not. Therefore, the author is interested in exploring the thoughts of scholars from the two schools which will be poured in the form of a scientific paper with the title Comparative Study between the Opinions of the Hanafi and Shafi'i Schools regarding the Concept of Zakat on Wealth of Children and Crazy People.